Secret of speed reading - Phatak, Shyam (Bangalore, 2004)
This book is beneficial to the Student and the Teacher, the Pupil and the Professor, the Junior Executive and the Top Boss, the Housewife and the Senior Citizen. It teaches a valuable skill that leads to success and satisfaction. In today's world, where there is an explosion of information, this book is a must-read for all.
Keywords: Reading; Speed Readig